67.2k views
2 votes
If f(x) = 5x – 1, then f^-1(x)=

If f(x) = 5x – 1, then f^-1(x)=-example-1

1 Answer

3 votes

Answer:


\boxed{\sf \ \ \ f^(-1)(x)=(x+1)/(5) \ \ \ }

Explanation:

hello

f(x)=5x-1

what can we say about
f^(-1)(x) ?


(fof^(-1))(x)=x=f(f^(-1)(x))=5f^(-1)(x)-1

so


5f^(-1)(x)-1=x\\<=> 5f^(-1)(x)-1+1=5f^(-1)(x)=x+1 \ \ \ add \ \ 1\\ <=> f^(-1)(x)=(x+1)/(5) \ \ \ divide \ \ by \ \ 5

hope this helps

User Jack Morrison
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.